Perhitungan Medan Listrik dan Rapat Arus pada Plasma Lucutan Korona dengan Konfigurasi Jarum–Cincin - Sutanti, Ratna Wulan; Wardaya, Asep Yoyo; Nur, Muhammad (JURNAL SAINS DAN MATEMATIKA, 2014)
This paper presents analytical method for the calculations of the electric field and current density in needle-ring configurations of the corona discharge plasma. The needle is considered hyperboloidal. The result of the calculation indicates that the strong electric field generated by the sharp needle due to the unsymmetrical of geometric form of it. Similarly, the current density at the tip of the sharp needle is higher than at the ring. The value of the electric field and current density depends on geometric form, especially radius of the hyperbola, radius of the ring, and the distance between the electrodes. Radius of the hyperbola must be smaller than radius of the ring. Â Keywords : electric field, current density, needle-ring configurations, geometric form